Socialization and Learning of Foreign Adult Learners: Challenges and Needs - Tereza Cristina C. Valverde (Adult Education Research Conference, 2014)
Adult foreign learners in higher education face challenges to integrate into the academic community. Strategies such as engaging in mentorship, sharing cultural traits, participating in service-learning programs and in the Academic and Learning Assistance centers can improve socialization and learning of foreign learners.